2016
DOI: 10.1186/s12888-016-1027-y
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for identification and treatment of individuals with attention deficit/hyperactivity disorder and associated fetal alcohol spectrum disorders based upon expert consensus

Abstract: BackgroundThe association of attention deficit/hyperactivity disorder (ADHD) and fetal alcohol spectrum disorders (FASD) results in a complex constellation of symptoms that complicates the successful diagnosis and treatment of the affected individual. Current literature lacks formal guidelines, randomized control trials, and evidence-based treatment plans for individuals with ADHD and associated FASD. Therefore, a meeting of professional experts was organized with the aim of producing a consensus on identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Instead a consensus of practice-based evidence currently guides the treatment of comorbid FASD and ADHD. [29] These areas highlight that while globally much work has been done to improve the quality of life and understanding of FASD, there is a need to systematically and robustly evaluate interventions. This needs to be appropriately funded to develop gold standard evidence that can inform guidance development groups, such as the UK National Institute for Health and Care Excellence (NICE).…”
Section: Interventions Following Identificationmentioning
confidence: 99%
“…Instead a consensus of practice-based evidence currently guides the treatment of comorbid FASD and ADHD. [29] These areas highlight that while globally much work has been done to improve the quality of life and understanding of FASD, there is a need to systematically and robustly evaluate interventions. This needs to be appropriately funded to develop gold standard evidence that can inform guidance development groups, such as the UK National Institute for Health and Care Excellence (NICE).…”
Section: Interventions Following Identificationmentioning
confidence: 99%
“…However, the present study found that the only parenting support offered was generic, which is inadequate for children with FASD as they require different parenting strategies to typically developing children (Paley and O'Connor, 2009;Rutman and van Bibber, 2010). As family support networks and non-pharmacological treatments are recommended for families of children with neurodevelopmental disorders (Hall and Graff, 2011;Young, et al, 2016), it would be beneficial if individuals within these networks were FASD aware as it would improve the efficacy of the support the children receive.…”
Section: Discussionmentioning
confidence: 73%
“…28 Nonresponse to stimulants has been suggested as a "red flag" for clinicians to consider ND-PAE/ FASD diagnosis and to explore other treatment considerations. 33 Clinicians should closely monitor and manage possible side effects of stimulants in children.…”
Section: Stimulantsmentioning
confidence: 99%